2018
DOI: 10.5056/jnm18029
|View full text |Cite|
|
Sign up to set email alerts
|

Potent Potassium-competitive Acid Blockers: A New Era for the Treatment of Acid-related Diseases

Abstract: Conventional proton pump inhibitors (PPIs) are used as a first-line therapy to treat acid-related diseases worldwide. However, they have a number of limitations including slow onset of action, influence by cytochrome P450 polymorphisms, unsatisfactory effects at night, and instability in acidic conditions. Alternative formulations of conventional PPIs have been developed to overcome these problems; however, these drugs have only introduced small advantages for controlling acid secretion compared to conventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
116
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 126 publications
(125 citation statements)
references
References 112 publications
(146 reference statements)
1
116
0
8
Order By: Relevance
“…VPZ was found to have a favorable safety and tolerability profile, which has also been observed in several other studies [16,17,42]. Mean morning fasting gastrin level after the administration of VPZ 20 mg for 4 weeks and VPZ 10 mg for 48 weeks was 977.2 pg/mL, which was similar to that in recent studies [18,19].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…VPZ was found to have a favorable safety and tolerability profile, which has also been observed in several other studies [16,17,42]. Mean morning fasting gastrin level after the administration of VPZ 20 mg for 4 weeks and VPZ 10 mg for 48 weeks was 977.2 pg/mL, which was similar to that in recent studies [18,19].…”
Section: Discussionsupporting
confidence: 87%
“…Although PPIs are used as the currently recommended first-line therapy for patients with GERD [5], these medications have a number of limitations including slow onset of action, unsatisfactory effects at night, influence by cytochrome P450 2C9 polymorphisms, and instability in acidic conditions [16,17,39,40]. The effect of VPZ 20 mg was attributed to its potent and rapid acid secretion-suppressive effects [41,42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Placebo‐controlled studies have shown that macrolides drive resistance in populations . Thus, dual vonoprazan and amoxicillin therapy for 2 weeks is a promising alternative treatment …”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35] Thus, dual vonoprazan and amoxicillin therapy for 2 weeks is a promising alternative treatment. [36][37][38] Nocturnal acid breakthrough (NAB) is another factor that may affect eradication rates. Kim et al 39 reported that the eradication rate among subjects without NAB was higher than that of patients with NAB.…”
Section: Dosage Of Antibioticsmentioning
confidence: 99%